Microbial Fermentation Assisted by Pulsed Electric Fields, Magnetic Fields and Cold Atmospheric Plasma: State of the Art - Nahed Yousfi; Nofel Merbahi; Jalloul Bouajila; Patricia Taillandier; Mohamed Debouba (Fermentation, 2025)
Microbial fermentation is a fundamental bioconversion mechanism widely used in diverse industrial sectors, notably in food processing and bioenergy production. Over the years, the wealth of information and scientific and technological advances in the field of fermentation have made considerable progress. Most recent research studies are currently devoted to the implementation of innovative technological processes in order to increase fermentation effectiveness while consuming less energy and processing time. The aim of the present review is to investigate the impact of innovative physical techniques (pulsed electric field, PEFs; cold atmospheric plasma, CAP; and magnetic fields, MFs) on fermentation processes. The bibliographic analysis will mainly focus on recent advances towards non-destructive methods (PEF, CAP, and MF) and their induced changes in fermentation dynamics, fermented product quality, metabolite synthesis, and microbial growth kinetics. Various databases, including PubMed, ScienceDirect, Google Scholar, ResearchGate, Scopus, and Web of Science, were used to collect pertinent scientific literature on the impact of innovative physical techniques on microorganisms and fermentation processes and to investigate the potential applications of these emerging technologies in the food and health sectors. According to the results, all techniques have the potential to optimize fermentation dynamics, boost metabolite synthesis, and enhance product quality. However, each technology displayed its own specific advantages and disadvantages.